Everything about Ukraine without Ukraine: Peace negotiations in Trump's brave new world - Sabine Fischer (Stiftung Wissenschaft und Politik (SWP), 2025)
For the past three years, Ukraine has not allowed Russia to win its illegal war of aggression. During long periods of the war, the parties have found themselves in a military and diplomatic stalemate. Now US President Donald Trump has sided with the aggressor. "Nothing about Ukraine without Ukraine", the principle that has guided Western policy since February 2022, no longer applies for Washington. Trump has fundamentally changed both the international environment in which war is taking place and the balance between the parties, paving the way for Russia to dictate the terms of peace. To prevent this from happening, swift and decisive European action is essential. The new German government must play a key role here - and it must do so from its very first day in office.
Keywords: 320; Ukraine; Russia; war of aggression; US President Donald Trump; Putin; stalemate; ceasefire; "Make America Great Again" (MAGA); Zelensky